2016
DOI: 10.21746/ijbio.2016.09.0012
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphics (finger prints) as predilection marker for impacted teeth: A randomized blind trial

Abstract: Impacted teeth are teeth which remain embedded in the jaws past their normal eruption time or which have been blocked from their normal eruption path because of crowding of adjacent teeth or lack of enough jaw size to accommodate their eruption. Impacted teeth can cause a number of problems if left in place. Dermatoglyphics is the study of skin patterns and finger ridges that present on the fingers, toes and the soles. Fingerprint patterns of both hands were analyzed among ten patients with impacted teeth seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…They concluded that in the group with impacted teeth, the tented arch pattern in both hands' index fingers was more common. 8 The non-randomization of the sampling in our study resulted in an unbalanced sex distribution, with female subjects being more likely than male subjects to be in the impacted third molar group. The compliance and patience of the subject during the procedure were the flaws in this investigation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They concluded that in the group with impacted teeth, the tented arch pattern in both hands' index fingers was more common. 8 The non-randomization of the sampling in our study resulted in an unbalanced sex distribution, with female subjects being more likely than male subjects to be in the impacted third molar group. The compliance and patience of the subject during the procedure were the flaws in this investigation.…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that in the group with impacted teeth, the tented arch pattern in both hands’ index fingers was more common. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016 Narang D et al, designed a study to make an observation of the usefulness of dermatoglyphic patterns in serving as a predictor for impacted teeth in population and to analyze fingerprint patterns in people with impacted teeth and compare them with people without impacted teeth 34 . They observed that loop pattern was observed slightly lower in the control group than that of Impacted Teeth group.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as a screening tool for identifying patients who are likely to develop disease. Since different genes influence the enamel by its chemistry or morphology, fingerprints can be considered as an indicator of dental abnormalities [10,13] . So the present study was carried out for studying the dermatoglyphic patterns of fingerprints of different age groups and to find the association of dermatoglyphic patterns with dental caries…”
Section: Introductionmentioning
confidence: 99%